LANGUAGE LEARNING STRATEGIES OF ESL LEARNERS AT MURRAY STATE UNIVERSITY IN IMPROVING THEIR ENGLISH LANGUAGE SKILLS - Rusnadi, Rusnadi (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
This mini research is intended to know the language learning strategies used by ESL students to improve their English language skills, and whether or not there is a different between male and female in the use of the strategies. The data were collected from 25 participants by using survey technique. The collected data were analyzed by using multiple regression analysis which includes Coefficients of Discrimination (r squared), Intercept Coefficients (the constant), and Variable Coefficients (slope), and then concluded inductively. The result of this study shows that strategies of language learning have significant influence to the improvement of students? language Skills, specifically for listening, speaking and reading. It is also conclude that there is no significant influence of strategy of learning to the improvement of vocabulary and writing skills. There is no significant difference of using strategy in relation with different genders (male & female). However, there is a slight difference between male and female in the use of reading strategies.